Pengaruh Kompetensi dan Insentif Terhadap Kinerja Karyawan PT. Manunggal Adi Jaya Permata Estate Kotabaru - Muhdar, Muhdar (Politeknik Negeri Madiun, 2022)
The purpose of this study was to determine the effect of competence and incentives on employee performance at PT. Manunggal Adi Jaya Permata Estate. The population in this study was 155 people, using the slovin formula, a sample of 62 people was obtained. Methods of data collection using a questionnaire. The data analysis technique uses multiple linear regression analysis, with the help of the SPSS for windows version 25 program. The results show that competence has no significant effect on employee performance, incentives have a significant effect on employee performance, competencies and incentives have a significant effect on employee performance simultaneously.